Recreational value of mountain biking at Putrajaya Challenge Park, Malaysia - Che Ibrahim, Nur Syuhada (2013)
This thesis focuses on using the travel cost method to value mountain biking activity in one of the adventure recreation development in this country, Putrajaya Challenge Park (PCP) where there has been little or no previous works of this kind conducted before. The government has spent a large amount of money, RM38 million to build PCP mainly for providing the opportunities for its users maximising their satisfaction and gain experience in recreational activities mainly MTB activity. Mountain bikers gain non-monetary benefits through their enjoyment of riding mountain bikes at PCP and they obtain satisfaction from their participation. Thus, an assessment of the estimated value of benefits from recreational opportunities at PCP must be made with the aim of justifying the usage of PCP as MTB site. An onsite survey was necessary in order to obtain the primary data for this study. The questionnaire used for the onsite survey was designed to capture the socio-economic variables about mountain bikers, mountain biking participation characteristic variables and travel cost component variables. The count data with a sample size of 302 that generated from the survey was modelled with the linear regression model. Based on this study, there were six factors found to be significant at 95% confidence level which affected the demand for mountain biking at PCP. The variables were time cost, on-site time, type of visitors, age, year’s participation and equipment cost. An estimate of consumer surplus (CS) per trip per user, as well as the total recreational value for 2011, was computed. The value estimated was RM90.91 per trip per user and the total recreational value for 2011 was RM 3, 63, 640.00. This value suggests that mountain biking has a significant value in the area and the management of PCP should be aware of the relative value of mountain biking when they make allocation decisions for the future development.